A transição é uma fuga: as poéticas do infinito y o fim da ontologia - Leal, Abigail Campos (2024)
The present study investigates how fugitive poetics, that is, people marked as black and indigenous by the Racial Event, and as trans by the Gender Binarism, shake the Western tradition of Ontology. thus, I investigate how Heidegger's existential analysis, in particular, Being and Time, Introduction to Metaphysics and Explanations of Hölderlin's poetry, engages with the question of the meaning of being, in its retreat to the Greek past as an original jump towards the European´s future, showing how the universal truth of being-exists is nothing more than the spiritual fiction of the white man's colonial expansion. the ontological difference, understood here as a violent separation between being and beings, cannot explain the existential complexity of fugitive poetics, firstly because its flesh and spirit are entangled. thus, the account of black and indigenous trans people, whose transition, which seems ontic according to ontology, alters not only their flesh, but transforms their spirit, ends up shaking the entire ontological architecture. furthermore, in the autobiographical account, as well as in black ancestral knowledge, such as in the Book of the Dead of the Kemita people and in the ancestral knowledge of the Yourubás, not only what the West calls being and spirit are inseparable, but existence is elaborated from of greater complexity than the ontological binarism of being and being. thus, I confront the ontological tradition, especially Heidegger, but secondarily Hegel and Aristotle, with the contemporary artistic and critical productions of fugitive poetics, dividing the study into an introduction that goes to the colonial foundation of ontology in a dialogue between Heidegger, the Ionian philosophers and the System of Mysteries of the Kemites, and three chapters, one on Being, another on Beings and the last on the World, all confronting fugitive poetics with existential analytics. the result is that, as ontology is the greatest foundation of Western metaphysics, as it is the elaboration of the foundation of physis (“nature”, “universe”), by shaking ontology, fugitive poetics announce nothing less than the end of the World as we know it